Immunohistochemical study of corneal inflammation after femtosecond laser clear corneal incisions or manual surgery. Issue 11 (November 2016) - Toto, Lisa; Curcio, Claudia; Mastropasqua, Alessandra; Mattei, Peter A.; D'Ugo, Erminia; De Nicola, Chiara; Mastropasqua, Leonardo
Abstract : Purpose : To use immunohistochemical staining to evaluate corneal inflammation and apoptosis induced after femtosecond laser incisions or manual incisions. Setting : Ophthalmology Clinic, University G. d'Annunzio, Chieti, Italy. Design : Experimental study. Methods : Ninety human cadaver corneas were cut manually or with the femtosecond laser at different energies and analyzed by immunohistochemistry after 5 minutes or 4 hours. The corneas were divided into 5 groups: untreated (Group 1), cut manually (Group 2), and treated with the femtosecond laser with increasing energies (Groups 3 to 5; 3.0 μJ, 6.0 μJ, and 15.0 μJ, respectively). Results : At 5 minutes, increased expression of interleukin (IL)‐18 was observed in the femtosecond laser groups compared with the manual group ( P < .01). Interferon gamma (IFNγ) positivity was significantly higher in Groups 4 and 5 than in Group 2 and between Groups 3 and 4 ( P < .05). The terminal uridine deoxynucleotidyl nick end‐labeling (TUNEL) positivity increased with higher energy (Group 2 versus Group 4 and Group 2 versus Group 5; P < .05). After 4 hours, IFNγ positivity was higher in Group 5 than in Group 2 ( P = .0021) and between Group 5 and Groups 3 and 4 ( P < .05). No sign of IL‐18 positivity was found after 4 hours in any sample. Group 5 showed significant higher TUNEL positivity than all other groups ( P < .0001). Conclusion : The femtosecond laser technique at high energies induced a higher corneal inflammatory response and a higher corneal cell apoptosis than the manual technique. Financial Disclosure : None of the authors has a financial or proprietary interest in any material or method mentioned.